2020
DOI: 10.5586/asbp.8914
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Knowledge of Wild Edible Plants of Biga (Çanakkale), Turkey

Abstract: Biga, located in the southwestern part of the Marmara Region of Turkey, is the largest district of Çanakkale. Wild edible plants and the ways in which they are used in Biga have not previously been documented. This ethnobotanical study of Biga was conducted between June 2011 and September 2014. In this study, we recorded information such as the local names of plants, the manner in which they are used, and the particular parts of the plants used. The cultural importance index was calculated for each taxon. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(95 reference statements)
0
3
0
1
Order By: Relevance
“…Further, recent ethnobotanical studies in the South Caucasus, especially in Georgia, have also revealed people's significant ethnobotanical knowledge related to wild edible plants (Bussmann, 2017;Bussmann, Paniagua Zambrana, Sikharulidze, Kikvidze, Darchidze, et al, 2020;Bussmann et al, 2016Bussmann et al, , 2017aBussmann et al, , 2017bBussmann et al, , 2018Hovsepyan et al, 2016;Łuczaj et al, 2017;Nanagulyan et al, 2020;Pieroni et al, 2020;. is area of high cultural importance of wild vegetables forms a belt stretching from the Mediterranean, through Turkey (e.g., Çakır, 2017;Ertuğ, 2004;Hançer et al, 2020;Yeşil & İnal, 2019) up to the Middle East and the Caucasus. However, only a few studies have documented wild edible plants in the Lesser Caucasus, Western Georgia, and Turkish Caucasus (Akgül, 2007;Bussmann et al, 2017a;Güneş & Özhatay, 2011;Kadıoğlu et al, 2020;Łuczaj et al, 2017;Özgen et al, 2004;Sağıroğlu et al, 2012;Saraç et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent ethnobotanical studies in the South Caucasus, especially in Georgia, have also revealed people's significant ethnobotanical knowledge related to wild edible plants (Bussmann, 2017;Bussmann, Paniagua Zambrana, Sikharulidze, Kikvidze, Darchidze, et al, 2020;Bussmann et al, 2016Bussmann et al, , 2017aBussmann et al, , 2017bBussmann et al, , 2018Hovsepyan et al, 2016;Łuczaj et al, 2017;Nanagulyan et al, 2020;Pieroni et al, 2020;. is area of high cultural importance of wild vegetables forms a belt stretching from the Mediterranean, through Turkey (e.g., Çakır, 2017;Ertuğ, 2004;Hançer et al, 2020;Yeşil & İnal, 2019) up to the Middle East and the Caucasus. However, only a few studies have documented wild edible plants in the Lesser Caucasus, Western Georgia, and Turkish Caucasus (Akgül, 2007;Bussmann et al, 2017a;Güneş & Özhatay, 2011;Kadıoğlu et al, 2020;Łuczaj et al, 2017;Özgen et al, 2004;Sağıroğlu et al, 2012;Saraç et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When we compare the taxa that we have determined to use as a nutrient in Yenice (Canakkale) with the taxa in the studies carried out in the nearby environment (Tutenocakli, 2002;Onar, 2006;Uysal et al, 2006;Satıl et al, 2007;Satıl et al, 2008;Bulut and Tuzlacı, 2009;Polat, 2010;Kökçü, 2015;Bulut, 2016;Gunes, 2017;Kızılarslan Hançer et al, 2020;Tanaydın et al, 2022), it is seen that they are similar. As a result, it is possible to say that these plants used for food are widely used in Turkey.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, wide range of recent studies reported the traditional cooking methods of stinging nettle leaves for human consumption. For example, the leaves and the aerial parts of stinging nettle: fresh leaves cooked as vegetable or dried leaves added to soup, especially in winter (Demir, 2020); leaves are used to prepare saag for remedy to Anthelmintic, antiseptic, dandruff, gout, nephritis sprain (Kumar, 2021); decoction and infusion (Maria S. González, García-Barriuso and Amich, 2010;Shonte, 2017); rst boiled and then fried with onions (Yesil and Inal, 2019), frequently used as green vegetable (Prakash et al, 2020); Sauteed in oil, added to pastry, fried with egg, boiled as salad and tea (Hançer et al, 2020); eaten raw, cooked with bulgur in Iğdır Province, Turkey (Çakir, 2017); roasted and then cooked, and boiled with oil and salt Vegetable (Ding et al, 2021). Local people have good knowledge of stinging nettles, including their time of availability, processing, and cooking method as well about their traditional medicinal value.…”
Section: Traditional Methods Of Preparing Stinging Nettle For Human Consumptionmentioning
confidence: 99%